Plastocyanin is the long-range electron carrier between photosystem II and photosystem I in plants - Höhner, Ricarda; Pribil, Mathias; Herbstová, Miroslava; Lopez, Laura Susanna; Kunz, Hans-Henning; Li, Meng; Wood, Magnus; Svoboda, Vaclav; Puthiyaveetil, Sujith; Leister, Dario; Kirchhoff, Helmut (Proceedings of the National Academy of Sciences of the United States of America, 2020)
In photosynthetic electron transport, large multiprotein complexes are connected by small diffusible electron carriers, the mobility of which is challenged by macromolecular crowding. For thylakoid membranes of higher plants, a long-standing question has been which of the two mobile electron carriers, plastoquinone or plastocyanin, mediates electron transport from stacked grana thylakoids where photosystem II (PSII) is localized to distant unstacked regions of the thylakoids that harbor PSI. Here, we confirm that plastocyanin is the long-range electron carrier by employing mutants with different grana diameters. Furthermore, our results explain why higher plants have a narrow range of grana diameters since a larger diffusion distance for plastocyanin would jeopardize the efficiency of electron transport. In the light of recent findings that the lumen of thylakoids, which forms the diffusion space of plastocyanin, undergoes dynamic swelling/shrinkage, this study demonstrates that plastocyanin diffusion is a crucial regulatory element of plant photosynthetic electron transport.
Keywords: Gene Expression Regulation, Plant; regulace genové exprese u rostlin; fotosystém I (proteinový komplex); Models, Biological; Photosystem II Protein Complex; Magnoliopsida; transport elektronů; fotosystém II (proteinový komplex); počítačová simulace; Computer Simulation; Plastocyanin; biologické modely; plastocyanin; Photosystem I Protein Complex; Electron Transport